Regulation of Hepatic UGT2B15 by Methylation in Adults of Asian Descent - Oeser, Steffen G. (Pharmaceutics, 2018)
The hepatic uridine 5′-diphosphate-glucuronosyl transferases (UGTs) are critical for detoxifying endo- and xenobiotics. Since UGTs are also dynamically responsive to endogenous and exogenous stimuli, we examined whether epigenetic DNA methylation can regulate hepatic UGT expression and differential effects of ethnicity, obesity, and sex. The methylation status of UGT isoforms was determined with Illumina Methylation 450 BeadChip arrays, with genotyping confirmed by sequencing and gene expression confirmed with quantitative reverse transcriptase polymerase chain reaction (q-RT-PCR). The UGT1A3 mRNA was 2-fold higher in females than males (p < 0.05), while UGT1A1 and UGT2B7 mRNA were significantly higher in Pacific Islanders than Caucasians (both p < 0.05). Differential mRNA or methylation did not occur with obesity. The methylation of the UGT2B15 locus cg09189601 in Caucasians was significantly lower than the highly methylated locus in Asians (p < 0.001). Three intergenic loci between UGT2B15 and 2B17 (cg07973162, cg10632656, and cg07952421) showed higher rates of methylation in Caucasians than in Asians (p < 0.001). Levels of UGT2B15 and UGT2B17 mRNA were significantly lower in Asians than Caucasians (p = 0.01 and p < 0.001, respectively). Genotyping and sequencing indicated that only UGT2B15 is regulated by methylation, and low UGT2B17 mRNA is due to a deletion genotype common to Asians. Epigenetic regulation of UGT2B15 may predispose Asians to altered drug and hormone metabolism and begin to explain the increased risks for adverse drug reactions and some cancers in this population.